Community mobilization in Mumbai slums to improve perinatal care and outcomes: a cluster randomized controlled trial. - Neena Shah More; Ujwala Bapat; Sushmita Das; Glyn Alcock; Sarita Patil; Maya Porel; Leena Vaidya; Armida Fernandez; Wasundhara Joshi; David Osrin (PLoS Medicine)
Introduction Improving maternal and newborn health in low-income settings requires both health service and community action. Previous community initiatives have been predominantly rural, but India is urbanizing. While working to improve health service quality, we tested an intervention in which urban slum-dweller women's groups worked to improve local perinatal health. Methods and findings A cluster randomized controlled trial in 24 intervention and 24 control settlements covered a population of 283,000. In each intervention cluster, a facilitator supported women's groups through an action learning cycle in which they discussed perinatal experiences, improved their knowledge, and took local action. We monitored births, stillbirths, and neonatal deaths, and interviewed mothers at 6 weeks postpartum. The primary outcomes described perinatal care, maternal morbidity, and extended perinatal mortality. The analysis included 18,197 births over 3 years from 2006 to 2009. We found no differences between trial arms in uptake of antenatal care, reported work, rest, and diet in later pregnancy, institutional delivery, early and exclusive breastfeeding, or care-seeking. The stillbirth rate was non-significantly lower in the intervention arm (odds ratio 0.86, 95% CI 0.60-1.22), and the neonatal mortality rate higher (1.48, 1.06-2.08). The extended perinatal mortality rate did not differ between arms (1.19, 0.90-1.57). We have no evidence that these differences could be explained by the intervention. Conclusions Facilitating urban community groups was feasible, and there was evidence of behaviour change, but we did not see population-level effects on health care or mortality. In cities with multiple sources of health care, but inequitable access to services, community mobilization should be integrated with attempts to deliver services for the poorest and most vulnerable, and with initiatives to improve quality of care in both public and private sectors. Trial registration Current Controlled Trials ISRCTN96256793